2016
DOI: 10.1007/s00709-016-0984-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the plant actin cytoskeleton response to applied pressure using nanoindentation

Abstract: Detection of potentially pathogenic microbes through recognition by plants and animals of both physical and chemical signals associated with the pathogens is vital for host well-being. Signal perception leads to the induction of a variety of responses that augment pre-existing, constitutive defences. The plant cell wall is a highly effective preformed barrier which becomes locally reinforced at the infection site through delivery of new wall material by the actin cytoskeleton. Although mechanical stimulation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Therefore, whether actin filaments or microtubules lead the organization in response to mechanical cues may be situation dependent. Interestingly, Branco et al 151 reported that the actin cytoskeleton aggregates beneath the location of experimentally induced nanoindentation in epidermal cells of Arabidopsis hypocotyls. The resulting actin response occurred at forces and in time frames considerably smaller than those required for microtubules 152,153 .…”
Section: Mechanoregulationmentioning
confidence: 99%
“…Therefore, whether actin filaments or microtubules lead the organization in response to mechanical cues may be situation dependent. Interestingly, Branco et al 151 reported that the actin cytoskeleton aggregates beneath the location of experimentally induced nanoindentation in epidermal cells of Arabidopsis hypocotyls. The resulting actin response occurred at forces and in time frames considerably smaller than those required for microtubules 152,153 .…”
Section: Mechanoregulationmentioning
confidence: 99%
“…It is known that actin organization is influenced by mechanical forces in animal cells ( 47 49 ), but how actin filaments respond to mechanical stresses has rarely been investigated in plants ( 50 52 ). Because the actin filaments and MTs have been shown to locate near the plasma membrane in plant cells, it has been suggested that the two networks interact ( 53 ).…”
mentioning
confidence: 99%
“…This work quantified the duration and magnitude of mechanical forces that can stimulate a structural defense response in a plant cell, representing the ultrastructural changes in response to pathogen invasion. [ 73 ] Dhanjai et al fabricated a stainless steel microneedle electrode by the layer‐by‐layer assembly for real‐time monitoring plant polyphenolics such as chlorogenic acid and gallic acid. In order to create a highly stable, sensitive, and conductive surface for antioxidant oxidation, the microneedles were manufactured with layers of carbon nanotube‐cellulose nanocrystal and polyaniline conductive polymer.…”
Section: Microneedle‐based Point‐of‐care Diagnostic Methodsmentioning
confidence: 99%
“…Isolation and detection of Phytophthora infestans (DNA-based pathogen) and tomato spotted wilt virus (RNA-based pathogen) from field-collected and laboratory-inoculated tomato leaves [55] Soils A gold-coated microneedle-based electrochemical sensors Detection of nitrate levels in soils based on microneedles and electrochemical sensors [68] Fish fillets Silk-based porous microneedle patch Detection of Escherichia coli contamination in fish fillets [69] Tomato stems Silicon microneedle device integrated with a micropatterned impedance measurement sensor Direct and real-time measurement of the electrical conductivity of the tomato stem [70] Cucumber stems Microneedle sensor with an electrode array Real-time measurement of the electrical conductivity in greenhouse-grown cucumber [71] Barley leaves Microneedle electrodes Monitor the bioimpedance of Barely leaves [72] Arabidopsis plants Tungsten microneedle Study the duration and magnitude of mechanical forces that can stimulate a structural defense response in a plant cell [73] Orange and kiwi fruits Stainless steel microneedle electrode Real-time monitoring of plant polyphenolics such as chlorogenic acid and gallic acid [74] Greenhouse tomato tree Microneedle thermal probe Noninvasive measurement of sap flow through the xylem for monitoring water transportation [76] Citrus seedlings (Citrus reshini, Cleopatra mandarin)…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%